2018
DOI: 10.1073/pnas.1716381115
|View full text |Cite
|
Sign up to set email alerts
|

Bilobal architecture is a requirement for calmodulin signaling to Ca V 1.3 channels

Abstract: Calmodulin (CaM) regulation of voltage-gated calcium (Ca) channels is a powerful Ca feedback mechanism that adjusts Ca influx, affording rich mechanistic insights into Ca decoding. CaM possesses a dual-lobed architecture, a salient feature of the myriad Ca-sensing proteins, where two homologous lobes that recognize similar targets hint at redundant signaling mechanisms. Here, by tethering CaM lobes, we demonstrate that bilobal architecture is obligatory for signaling to Ca channels. With one lobe bound, Ca car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 90 publications
5
15
0
Order By: Relevance
“…The detailed analysis of the channel gating with Ca 2þ as a charge carrier is in agreement with a new model of L-type Ca V channel regulation by CaM and, thus, supports the interpretation that high-CDI states and high-P O states correspond to the identical CaM-bound state (27,50,51). In this model, simultaneous binding of both C-and N-lobes of apoCaM to the proximal C-terminus of Ca V 1.3 channels is required for the switching of the channel gating from the basal low to the high-P O mode.…”
Section: Mechanismsupporting
confidence: 84%
See 1 more Smart Citation
“…The detailed analysis of the channel gating with Ca 2þ as a charge carrier is in agreement with a new model of L-type Ca V channel regulation by CaM and, thus, supports the interpretation that high-CDI states and high-P O states correspond to the identical CaM-bound state (27,50,51). In this model, simultaneous binding of both C-and N-lobes of apoCaM to the proximal C-terminus of Ca V 1.3 channels is required for the switching of the channel gating from the basal low to the high-P O mode.…”
Section: Mechanismsupporting
confidence: 84%
“…In our single-channel experiments, Ca V 1.3 42 channels spent $10% of the time in the high-P O state under basal conditions. Assuming 10% of all plasmalemmal Ca V 1.3 42 channels to hold CaM (i.e., to cause an about sevenfold higher peak current then the remaining 90% of the channels and to show a CDI value of $0.7 (27,37,50,51)), one calculates an apparent CDI of 0.3 for the whole ensemble of Ca V 1.3 42 channels. This agrees with the published values (27,33,37,38) explaining the only moderate inhibition of CDI by CTM in contrast to a nearly complete inhibition of CDI by CTM of Ca V 1.4 channels (32).…”
Section: Dynamic Competition Between Cam and Ctmmentioning
confidence: 99%
“…In addition, quantifying CDI from single-channel currents (CDI SCH ) poses a more general sampling challenge that relates to the random nature of the CaM/channel interaction (42,43). This randomness renders uncertain whether in any one recording, sufficient on/off events are captured to recapitulate the full range of kinetic changes and thus to converge on the macroscopically observed CDI WC .…”
Section: Revealing CDI Of Single Nmda Receptor Currentsmentioning
confidence: 99%
“…3) and is an essential property of calmodulin, which permits this protein to interact with a large and diverse array of partners. It has been recently demonstrated that calmodulin's bilobal architecture is essential for VGCC regulation (Banerjee et al 2018). The significant conformational changes on binding to its targets (Fallon et al 2005) can increase its affinity for Ca 2+ .…”
Section: Calmodulin the Physiology And Functions Of Calmodulinmentioning
confidence: 99%